Imaging studies used as aid in the diagnosis of cleidocranial dysplasia. A review - Granado-Abasto, Laura A. (2021)
Cleidocranial dysplasia (CCD), also known as Marie-Sainton syndrome, is a rare disorder of autosomal dominant type that presents specific characteristics at the skeletal and dental level. The diagnosis of CCD is based on clinical and radiographic findings. Panoramic, cephalometric, and anterior poster radiographs have been used for its diagnosis in dentistry. However, these radiological techniques have limitations, and advances in technology with new imaging studies such as magnetic resonance imaging (MRI) and ultrasound have emerged, contributing to the diagnosis of CCD. Therefore, the aim of this review was to identify and describe current imaging studies that contribute to both the diagnosis and adequate and efficient treatment planning of CCD and describe the clinical and radiographic characteristics of patients with this syndrome.